El Nino visto por las ciencias sociales: propuestas de investigacion, climatic and hydrological effects of El Nino Southern Oscillation (ENSO) events at regional and local scales - Katz, E.; Goloubinoff, M.; Lammel, A. (1998)
Until now, the El Nino has mainly been studied by natural scientists. From their experiences in the study of the relationship between societies and their climatic environment (Gloubinoff, Katz & Lammela, 1997), the authors propose that social scientists be included in future research projects dealing with this theme. They show the different aspects in which these scientists could complement and enrich other scientific approaches that often give a global view of the ENSO from the physical perspectives of the sky, the sea or the earth. Focused on human beings, the social sciences tend to approach the problem at a local level. First, research could be conducted on local history of floods and drought, through oral tradition, archives and archaeology. Second, in most societies, people have developed a good indigenous knowledge of the local climate, its variations, seasons, meteorological phenomena, climate change and weather forecasting. Anthropologists, for instance, can interpret the logic of this knowledge beyond its symbolic elements, to enhance the understanding of indigenous knowledge by other scientists. It could aise be interesting to be aware of how populations affected by El Nina perceive that phenomenon, which carries a mythical name given by the coastal inhabitants of South America. Understanding how these populations interpret news on El Nino, as conveyed by the mass media, would bring the problem a step forward and allow the media to pass on better data and forecasting to the affected people. Third, the environmental and social consequences of the El Nino phenomenon should be recognized, as well as the rote of human responsibility in the consequences, as was recently shown in the case of forest fires in Indonesia